Keterbukaan Diri Mahasiswa Rantau Dengan Pola Asuh Orang Tua Otoriter - Amaliah, Siti Hikmah; Shabrina, Almira (eProceedings of Management, 2024)
In generally, nomadic students decrease their communication patterns with their parents. In the case of parents withstrict parenting patterns, this will become an obstacle to the decreasing pattern of communication and self-disclosureamong students.This research aims to find out how self-disclosure occurs between nomadic teenagers who areexperiencing a phase and parents with strict parenting patterns. This research uses a qualitative method through aphenomenological approach carried out with seven informants consisting of three key informants from nomadicstudents at Telkom University, three supporting informants from the parents of the key informants, and one expertinformant in the field of adolescent and family psychology. The results of the research show that nomadic teenagersin the phase feel free from the reach of their parents but don’t create self-disclosure. It’s indicated by the interviewresults, which show that the communication between the children and their parents isn’t open because the children feelconstrained by their parents' strict rules. Keywords-self disclosure, authoritarian, adolescents.